The significance of policy and guidelines on risk management implementation and development in malaysian and United Kingdom public sector - Abdul Gani, Ahmad Shukri; Salim, Basariah; Mat Udin, Noraza (Science Publishing Group, 2020)
The purpose of this paper was to identify the significance of the policy and guidelines on risk management implementation and development in the public sector. Specifically, this paper compared the risk management implementation in the Malaysian and United Kingdom public sector by emphasizing the significance of policy and guidelines. Archival documents from government websites and relevant government agencies in Malaysia and United Kingdom were collected and critically analyzed. This study found that policy and guidelines are significant in risk management implementation and development in the public sector context. The central government policy is classified as the most powerful element as compliance with regulation is the dominant factor driving risk control systems in many organizations. In addition, suitable guidelines ensure organizations have good risk management practices and not just a one-off exercise, to facilitate the development of sustainable processes of risk management. The Malaysian government needs to decide to adopt a more formal and structured approach to risk management by incorporating the best practices from the private sector and benchmarks from a variety of public sector organizations around the world, such as the United Kingdom. The relevant guides and reports should be prepared by adopting various methods to contribute toward the development of risk management in Malaysian public sector.